2010
DOI: 10.1524/ract.2010.1685
|View full text |Cite
|
Sign up to set email alerts
|

Study of transfer of minor elements during ironmaking by neutron activation analysis

Abstract: Neutron activation analysis / Minor elements / Metallurgical samples / Iron and steel industrySummary. In this work instrumental neutron activation analysis (INAA) was applied to investigate a total of 30 samples of metallurgical raw materials (sinter, pellets, coke) and related finished products (pig iron, slag, blast-furnace flue dust) sampled from the same blast furnace discharge in the ironmaking process in the Integrated Iron and Steel Works of Galati (Romania). The transfer efficiencies of minor elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…5 and 6) (Ene et al 2009). Many reasons have been given for this decrease in heavy metal concentration with increase in depth.…”
Section: Resultsmentioning
confidence: 98%
“…5 and 6) (Ene et al 2009). Many reasons have been given for this decrease in heavy metal concentration with increase in depth.…”
Section: Resultsmentioning
confidence: 98%
“…However, they are dangerous due to the unstable subsoil. It was found that the radioactivity of iron slag in Slovakia [5,6] and in Romania [7] does not exceed the limit permitted by the legislation.…”
Section: Introductionmentioning
confidence: 97%
“…X-rays fluorescence (XRF) is an analytical method widely used for the quantitative and qualitative determination of the elementary chemical composition of samples with a variable number of elements. The great advantage of this method of analysis results from the fact that the samples, mainly the metallic ones and the powders, are not destroyed during the analysis and do not require a prior chemical treatment [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%